2005
DOI: 10.1101/gad.1371305
|View full text |Cite
|
Sign up to set email alerts
|

Global changes in STAT target selection and transcription regulation upon interferon treatments

Abstract: The binding of transcription factors to specific DNA sequences determines the populations of target genes to be expressed and how their transcription is regulated. Mapping transcription factor-binding sites and identifying these target genes remains an imposing obstacle to understanding the complex nature of gene regulatory networks. Furthermore, identification of the sites bound by transcription factors under different activation conditions is necessary to fully address many questions regarding transcriptiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
80
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 100 publications
(85 citation statements)
references
References 54 publications
5
80
0
Order By: Relevance
“…On the other hand, Wajapeyee et al (2008) reported that IGFBP7 induces apoptosis through increased SMARCB1 upregulation by the recruitment of STAT1 to the binding site of the SMARCB1 promoter. Another study reported that STAT1 is recruited to the SMARCB1 promoter by IFN, suggesting that IFN-induced STAT1 recruitment to the SMARCB1 promoter is possibly one of the mechanisms of IFN-induced apoptosis (Hartman et al, 2005). It might therefore be possible that STAT1 recruitment could be prevented antagonistically when IGFBP7 is suppressed, leading to a higher resistance to IFN-a than to other drugs.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Wajapeyee et al (2008) reported that IGFBP7 induces apoptosis through increased SMARCB1 upregulation by the recruitment of STAT1 to the binding site of the SMARCB1 promoter. Another study reported that STAT1 is recruited to the SMARCB1 promoter by IFN, suggesting that IFN-induced STAT1 recruitment to the SMARCB1 promoter is possibly one of the mechanisms of IFN-induced apoptosis (Hartman et al, 2005). It might therefore be possible that STAT1 recruitment could be prevented antagonistically when IGFBP7 is suppressed, leading to a higher resistance to IFN-a than to other drugs.…”
Section: Discussionmentioning
confidence: 99%
“…For RNA Pol II and normal mouse IgG ChIP samples, 12 g of either the mouse monoclonal 8WG16 antibody (Covance MMS-126R) or normal mouse IgG (Santa-Cruz sc-2025) were added to 1 ϫ 10 8 cells. ChIPs were conducted as previously described (21,22). Libraries were constructed in a manner consistent with those from Rozowsky et al (8).…”
Section: Methodsmentioning
confidence: 99%
“…In this scenario, pathogenic CCD mutations might not only influence innate STAT1 activity but also reconstitute the repertoire of STAT1 target genes by altering assembly of the transcription factor complexes (19). To examine this hypothesis, we performed RNA-seq analysis of R274Q-modulated transcription.…”
Section: Impact Of An Arg-274 Mutation On the Genome-wide Expression mentioning
confidence: 99%